2023
DOI: 10.1007/s11739-023-03283-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the efficacy and safety of SARS-CoV-2 vaccination in residents of long-term care facilities: insights from the GeroCovid Vax study

Abstract: Despite the reported sex-related variations in the immune response to vaccination, whether the effects of SARS-CoV-2 vaccination differ by sex is still under debate, especially considering old vulnerable individuals, such as long-term care facilities (LTCFs) residents. This study aimed to evaluate COVID-19 infections, adverse events, and humoral response after vaccination in a sample of LTCF residents. A total of 3259 LTCF residents (71% females; mean age: 83.4 ± 9.2 years) were enrolled in the Italian-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Data from older patients in a long-term care facility showed that the response to COVID-19 vaccination at 7 days and 1 year after vaccination was similar regardless of gender, although antibody titers varied depending on specific comorbidities. Additionally, female subjects experienced localized adverse side effects at the vaccination site ( Trevisan et al, 2023 ).…”
Section: Immune Aging According To Sex and Gendermentioning
confidence: 99%
“…Data from older patients in a long-term care facility showed that the response to COVID-19 vaccination at 7 days and 1 year after vaccination was similar regardless of gender, although antibody titers varied depending on specific comorbidities. Additionally, female subjects experienced localized adverse side effects at the vaccination site ( Trevisan et al, 2023 ).…”
Section: Immune Aging According To Sex and Gendermentioning
confidence: 99%